2017
DOI: 10.5530/ijper.51.3s.53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Plant Essential Oils against Fungi on Wheat Seeds

Abstract: Diseases, especially caused by seed borne fungi, are among the factors decreasing yield and quality of wheat. Common bunt is also an important seed borne disease of wheat worldwide. The objective of the study is to determine the effects of clove, ginger, mint, oregano and thyme oils on the fungal load of wheat seeds. In addition, effects of the oils on the germination rates of bunt spores were investigated. Blotter method was used to determine the effects of different concentrations (0.05 -10%) of the oils on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…This mycotoxin has carcinogenic, teratogenic and immunotoxic effects for rats and probably human [3]. Regarding to the adverse effects of fungicides on health and the environment, and on the resistance of strains to drugs and synthetic chemical compounds, researchers have focused on more natural and safe chemical compounds [6][7][8]. Studies have revealed that secondary metabolites of many plants are capable of preventing the growth of fungi.…”
Section: Introductionmentioning
confidence: 99%
“…This mycotoxin has carcinogenic, teratogenic and immunotoxic effects for rats and probably human [3]. Regarding to the adverse effects of fungicides on health and the environment, and on the resistance of strains to drugs and synthetic chemical compounds, researchers have focused on more natural and safe chemical compounds [6][7][8]. Studies have revealed that secondary metabolites of many plants are capable of preventing the growth of fungi.…”
Section: Introductionmentioning
confidence: 99%
“…S tim u vezi, primena preparata na bazi biljaka, uključujući i produkte njihovog sekundarnog metabolizma, posebno etarska ulja, sve više dobija na značaju (Marković, 2011). Etarska ulja su aromatična i lako isparljiva, kompleksna prirodna jedinjenja za koje postoje podaci da utiču na inhibiciju zaraze semena gajenih biljaka u manjoj ili većoj meri (Karaca et al, 2017), što je potvrđeno i u ovom istraživanju.…”
Section: Hemijski Sastav Etarskog Uljaunclassified
“…Zahvaljujući novim pravcima, potreba za proučavanjem i primenom etarskih ulja i biljnih ekstrakata u zaštiti gajenog bilja od bolesti se povećava i sve više dobija na značaju. Njihova primena u zaštiti semena gajenih biljaka, može uticati kako na klijanje, tako i na smanjenje zaraze semena patogenima (Karaca et al, 2017). U istraživanjima Montes-Belmont i Carvajal (1998), etarsko ulje pitome nane bilo je testirano u zaštiti semena kukuruza od patogene gljive Aspergillus flavus, dok su Karaca et al (2017) etarsko ulje pitome nane koristili za tretiranje semena pšenice protiv patogenih vrsta iz rodova Tilletia, Alternaria i Aspergillus.…”
unclassified
See 1 more Smart Citation
“…Mahmood et al, [23] stated that pest management using biopesticides is an age long tradition especially among rural dwellers [24], until the recent introduction of synthetic pesticides where the former was considered ineffective especially in the management of major pest and disease of pandemic magnitude such as rusts and blights [12] which required quick action and wide coverage area. However, the threat to both environment and human health attributed to the synthetic pesticide has called for man to advocate the use of natural plant material in pest management to overcome the dangers of hazardous chemical pesticide residues in foods and feed stuffs which are usually above the minimum residual or permissible levels in food and feed stuffs [25][26][27]. Biopesticides are capable of repelling, inhibiting growth or killing pests [28].…”
Section: Introductionmentioning
confidence: 99%